Immunotherapy-related hepatitis: real-world experience from a tertiary centre. Issue 4 (22nd March 2019) - Cheung, Vincent; Gupta, Tarun; Payne, Miranda; Middleton, Mark R; Collier, Jane D; Simmons, Alison; Klenerman, Paul; Brain, Oliver; Cobbold, Jeremy F
Abstract : Objective: Immune checkpoint inhibitors like anti-programmed cell death protein 1 (PD-1) drugs Nivolumab and Pembrolizumab and anti-cytotoxic T-lymphocyte associated (CTLA-4) drug Ipilimumab have become standard of care in many metastatic cancers. Immunotherapy-related hepatitis and cholangitis present a diagnostic and management challenge, being rare and incompletely characterised. We aim to report the incidence, features and treatments used for this in a real-world setting and to identify useful biomarkers, which can be used to predict effective use of steroids. Design: Retrospective review of 453 patients started on immunotherapy over 7 years. Setting: Tertiary hepatology and oncology centre. Patients: 21 patients identified with immunotherapy-related hepatotoxicity. Results: Hepatitis was most common in those receiving dual therapy (incidence 20%), with 75% of Grade 4 hepatitis cases occurring with ipilimumab-containing regimens. Corticosteroid monotherapy is first line treatment, but doses above 60 mg OD prednisolone do not demonstrate any additional benefit in time to hepatitis resolution. The alanine transaminase (ALT) reduction in steroid-responsive hepatitis is typically rapid (with a halving of ALT within 11 days). The commencement of additional immunosuppression (typically mycophenolate) appears safe and prompts a more rapid fall in ALT than corticosteroid use alone. Infliximab was safely used twice as hepatitis treatment. We also describe one patient with rare immunotherapy-induced biliary disease. Conclusions: Vigilance is required for detection of immunotherapy-associated liver disease as, other than dual immunotherapy, we can identify no predictive factors for its development. Our data suggest that corticosteroid response is not dependent on the higher dosing regimens. Early escalation of immunosuppression may be of benefit in the absence of a rapid response to corticosteroids.